Synaptic Vesicle Recycling and the Endolysosomal System: A Reappraisal of Form and Function - Ivanova, Daniela; Cousin, Michael A. (Frontiers in Synaptic Neuroscience, 2022)
The endolysosomal system is present in all cell types. Within these cells, it performs a series of essential roles, such as trafficking and sorting of membrane cargo, intracellular signaling, control of metabolism and degradation. A specific compartment within central neurons, called the presynapse, mediates inter-neuronal communication via the fusion of neurotransmitter-containing synaptic vesicles (SVs). The localised recycling of SVs and their organisation into functional pools is widely assumed to be a discrete mechanism, that only intersects with the endolysosomal system at specific points. However, evidence is emerging that molecules essential for endolysosomal function also have key roles within the SV life cycle, suggesting that they form a continuum rather than being isolated processes. In this review, we summarise the evidence for key endolysosomal molecules in SV recycling and propose an alternative model for membrane trafficking at the presynapse. This includes the hypotheses that endolysosomal intermediates represent specific functional SV pools, that sorting of cargo to SVs is mediated via the endolysosomal system and that manipulation of this process can result in both plastic changes to neurotransmitter release and pathophysiology via neurodegeneration.